Research on cutting characteristics of fiber bundle with high-speed photography - He, Zhitao; Ding, Huiling; Du, Sanming; Li, Zhen; Ji, Jiangtao; Li, Jian; Zhang, YongZhen (International Journal of Agricultural and Biological Engineering, 2020)
Cutting is an essential and complicated process in many fields. Efficient and low-consumption cutting operations are of great significance for environmental protection and energy conservation. The development of high performance cutting parts relies on a deep understanding of the cutting process and cutting mechanism. In this research, a new type of cutting test bench with high-speed photography was developed, and the cutting tests were conducted on the jute fiber bundle from quasi-static cutting at 10 mm/s to dynamic cutting in the speed range of 0.6-2.4 m/s. The cutting process was captured by a high-speed camera. Analysis shows that compression exists before quasi-static cutting, and the compression force curve with respect to the compression ratio follows an exponential function. The cutting speed has a significant effect on cutting energy. The cutting energy consumption is not a monotonous function of cutting speed owing to the combined effect of elastic deformation and friction of fibers. The cutting energy increases with increasing cutting speed in the range of 0.6-1.2 m/s due to the increase of the friction within fibers and the friction between the blade and fibers. The cutting energy decreases with increasing cutting speed in the range of 1.2-1.8 m/s, and tends to be a fixed value when the cutting speed exceeds 1.8 m/s due to the stabilized elastic deformation and friction coefficient. From the perspective of energy saving, it is meaningless to increase the blade speed excessively when cutting fiber bundles.Keywords: jute fiber, cutting, high-speed photography, energy consumption, frictionDOI: 10.25165/j.ijabe.20201303.5677Citation: He Z T, Ding H L, Du S M, Li Z, Ji J T, Li J, et al. Research on cutting characteristics of fiber bundle with high-speed photography. Int J Agric & Biol Eng, 2020; 13(3): 94–99.